2019
DOI: 10.1186/s12894-019-0466-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of staged buccal mucosal graft for repair of long segment anterior urethral stricture

Abstract: Background Long anterior urethral stricture due to variable etiological factors constitutes a challenge for reconstruction. We evaluated our centers experience with cases of long anterior urethral stricture due to different etiologies that were managed by 2-stage substitution urethroplasty using buccal mucosal graft procedure. Methods During the period between November 2009 and November 2016. All cases with long anterior urethral stricture that were planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…The key points in the first‐stage surgery are opening of the scarred urethra until the healthy urethra is reached to ensure complete engraftment in the region near the stoma, and to carefully create the stoma by suturing graft to the skin 19 . Even if the first‐stage surgery is perfectly carried out in this manner, it is not uncommon to encounter stomal stenosis caused by annular contracture 2,7,23 . Recent studies reported that after the first‐stage surgery, revision surgery is required in 6.7–59% of patients to repair contracture and/or stomal stenosis 2,3,7,11,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The key points in the first‐stage surgery are opening of the scarred urethra until the healthy urethra is reached to ensure complete engraftment in the region near the stoma, and to carefully create the stoma by suturing graft to the skin 19 . Even if the first‐stage surgery is perfectly carried out in this manner, it is not uncommon to encounter stomal stenosis caused by annular contracture 2,7,23 . Recent studies reported that after the first‐stage surgery, revision surgery is required in 6.7–59% of patients to repair contracture and/or stomal stenosis 2,3,7,11,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The penile complications in a series of buccal mucosa urethroplasty [7] was, wound dehiscence in 2 (1.9%) patients, re-stricture in 11 (10.5%), fistula in 6 (5.7%) patients, meatal stenosis in 3 (2.9%).…”
Section: Discussionmentioning
confidence: 99%
“…e properties of buccal mucosa such as the absence of hair follicle, highly vascular lamina propria promoting early in growth, wet environment compatibility [12], and ease of harvest with a concealed donor site scar makes it a near ideal substitute for urethra. e incidence of graft contracture in BMG urethroplasty varies from 3 to 22.5% in various studies [13][14][15][16][17][18]. Oral mucosal grafts are also used in the ocular reconstructive Advances in Urology surgeries [19].…”
Section: Discussionmentioning
confidence: 99%